TINJAUAN HUKUM PIDANA TERHADAP PENGGUNA JASA PROSTITUSI ONLINE - Husnulwati, Sri (Faculty of Law, University of Palembang, 2019)
Looking at the articles in the Criminal Code, there are no articles that can be used to ensnare users of commercial sex services or commercial sex workers themselves. If referring to the law, of course, the targeted parties are only brokers and pimps. This study tries to see how the criminal law foundation can be used to ensnare users of online prostitution services. This research is a type of legal research which is also referred to as empirical legal research. The results of this research are, (1) Law No. 11 of 2008 concerning Information and Electronic Transactions is not appropriate to be used to deal with complex prostitution issues, (2) Law Number 44 of 2008 on Pornography does not explain specifically about users of online prostitution services, so in this case the Act cannot ensnare service users in the practice of online prostitution.